Hemocompatibility in hemodialysis and erythropoietin therapy - Opatrný, K; Vít, L; Opatrná, S; Polakovic, V; Sefrna, F; Sulková, S; Opatrný, K (Artificial organs, 1995)
Two studies designed to investigate the effect of recombinant human erythropoietin (rHuEPO) treatment of anemia in chronic dialysis patients on hemocompatibility were conducted. Study 1, whose main aim was to establish whether treatment with rHuEPO enhances coagulation activation during dialysis, included 15 patients before rHuEPO therapy at a mean hematocrit (HCT) of 22.3% and then during therapy at a HCT of 29.3%. The plasma concentrations of the thrombin-antithrombin III complex were not higher during rHuEPO therapy than before it when performing hemodialysis with a Cuprophan membrane. No significant difference was demonstrated either in the values of activated clotting times (Hemochron), thrombocyte or white blood cell counts (Coulter S+II), or in plasma C5a concentrations (ELISA) established during dialysis sessions before and during rHuEPO therapy. In Study 2, which focused primarily on the question of whether or not rHuEPO therapy increases thrombocyte activation during hemodialysis, 8 patients on chronic dialysis were examined both before therapy at a mean HCT value of 22.1% and during rHuEPO therapy at a HCT of 31.5%, invariably during dialysis with either a Cuprophan or polyacrylonitrile (AN69HF) membrane. The plasma concentrations of beta-thromboglobulin (ELISA) did not differ between the examinations made during rHuEPO and before rHuEPO therapy; however, statistically significant differences were found between dialysis sessions involving Cuprophan and AN69HF membranes. No significant difference between examination before and during rHuEPO was demonstrated in activated clotting time nor thrombocyte and white blood cell counts in this study either. The authors conclude that rHuEPO therapy does not enhance coagulation activation during hemodialysis, does not have an effect on thrombocyte activation, and does not influence complement activation and changes in white blood cell counts.
Keywords: Histocompatibility; akrylové pryskyřice; Humans; Complement C5a; beta-Thromboglobulin; erythropoetin; lidé středního věku; membrány umělé; Renal Dialysis; celulosa; Female; komplement C5a; dospělí; trombocyty; ELISA; krevní proteiny; dialýza ledvin; lidé; Erythropoietin; Recombinant Proteins; Enzyme-Linked Immunosorbent Assay; histokompatibilita; Acrylic Resins; Adult; Blood Proteins; rekombinantní proteiny; Blood Platelets; ženské pohlaví; beta-thromboglobulin; Male; Middle Aged; Cellulose; Membranes, Artificial; mužské pohlaví